Isolation of Bacillus subtilis mutants altered in expression of a gene transcribed in vitro by a minor form of RNA polymerase (E-sigma 37). - Truitt, C L (1985)
To develop a technique for identifying Bacillus subtilis genes whose products affect transcription from promoters recognized by sigma 37-containing RNA polymerase (E-sigma 37), we cloned the promoter region of a gene (ctc) that is actively transcribed in vitro by E-sigma 37 into a plasmid (pPL603B) so that a transcriptional fusion was created between ctc and a plasmid-borne chloramphenicol acetyltransferase (CAT) gene. CAT levels in B. subtilis carrying the ctc/CAT fusion plasmid varied in a manner that was consistent with the known pattern of ctc RNA synthesis. Mutagenesis of cells harboring the ctc/CAT plasmid led to the isolation of bacterial clones which displayed altered chloramphenicol resistance. Analysis of the mutants demonstrated that CAT activity was substantially changed in the mutant cells. Several of the B. subtilis mutants, both CAT overproducers and underproducers, also had acquired a sporulation-deficient phenotype. The mutations responsible for altered CAT expression were not carried on the plasmid. Analysis of RNA synthesized by mutant cells indicates that at least a portion of the mutants may be altered in the level of transcription from the ctc promoter and, hence, are likely to define B. subtilis genes which influence this process.